Paciente Masculino De 45 Años De Edad Con Síndrome Metabólico - Moreta Ruiz, Joselyn Juliana (2018)
The present case study is based on a 45-year-old male patient, diagnosed with metabolic syndrome, family history of Diabetes Mellitus, ischemic heart disease, physical examination reveals high blood pressure, in the anthropometric assessment reveals body mass index of 31kg / m2, according to the points of cuts of the World Health Organization, with nutritional status of Obesity Grade I. the integral nutritional diagnosis is made through the evidence of anthropometric parameters, the biochemical values reveal high lipid profile, high fasting glycemia, in the dietary evaluation and / or food Anamnesis evidence of excessive energy intake and macronutrients. It aims to improve the nutritional status of the patient through a correct nutrition intervention, 2080 kcal / day feeding plan, low fat, high fiber, control of sodium, potassium, vitamin C, divided into 5 meals a day according to your requirements caloric, with the emphasis on preventing cardiovascular risks aggravate aggressively, managing to improve the quality of life of the patient and avoid complications.